Critical Historiographical Analysis of Philip K. Hitti’s History of The Arabs: An Examination of Positionalism and Arab Historical Narratives: Analisis Historiografi Kritis terhadap History of The Arabs karya Philip K. Hitti: Telaah atas Posisionalitas dan Narasi Sejarah Arab - Muh Zulkifli; Dewi Anggariani; Musafir Pababbari (Indonesian Journal of Islamic History and Culture, 2026)
Philip K. Hitti's History of the Arabs (1937) is a canonical work that shaped the Western understanding of Arab history. This article presents a historiographical critique of the text using Edward Said's Orientalism, Michel-Rolph Trouillot's concept of silencing, and Chase F. Robinson's study of Islamic historiography. The analysis reveals that while Hitti's work aimed to reclaim Arab history from Orientalist bias, it remained trapped within the same discursive logic. Its "rise and fall" narrative systematically silences the Ottoman period, reflecting both Hitti's Arab nationalist bias and his Christian sectarian perspective as a Maronite. Moreover, his philological method disregards the epistemology of classical Islamic historiography. The article concludes that the current significance of Hitti's work lies not in its factual authority, but as a mirror of intellectual ambivalence in the late colonial era.